ISLAM NUSANTARA: PREJUDICE AND SOCIAL CONFLICT - Reza Fahmi; Prima Aswirna (State Institute of Islamic Studies (IAIN) Palu, 2019)
This research is based on the fact that there are religious leaders and some people who oppose the idea of Islam Nusantara. When the religious figure represented a formal legal institution (MUI), it had a significant influence on the views of the people of Padang. Therefore, the polemic of Islam Nusantara gives its own style about the existence of Islam Nusantara in the land of Minang. Further research objectives: (1) Describe the prejudices of community leaders about Islam Nusantara. (2) Describe the picture of people's prejudices about Islam Nusantara. (3) Connecting the prejudices of religious leaders and the community and its relation to the social conflict of the people of Padang City. The study uses qualitative approaches and quantitative mixing methods (mixed method). The population in this study were 32 religious leaders and 168 community members. Data collection techniques using; observation, interview and psychological scale. The sampling technique is random sampling technique. Data analysis techniques using Pearson correlation (Pearson correlation). The results of this study found that generally the negative prejudices of religious leaders about Islam Nusantara were high. While social conflict in the midst of society is classified as low. Whereas the correlation aspect shows that there is no relationship between community’s prejudices about Islam Nusantara and social conflict in the midst of society.